PENGARUH PENGGUNAAN FACEBOOK SEBAGAI MEDIA PEMBELAJARAN TERHADAP HASIL BELAJAR MAHASISWA - Rohmah Indahwati; Hasan Basri (Universitas Muhammadiyah Ponorogo, 2017)
This study aims to determine (1) the influence of social usage of Facebook on student learning outcomes, (2) student response in solving problems using Facebook and (3) obstacles and suggestions in implementing learning using social networking site Facebook. This finding is useful for educators to make Facebook as one of the media that can be used in teaching. This study is a combined study between quantitative and qualitative research. Quantitative research methods with the use of quasi-experimental, while the qualitative data obtained from the observation data and questionnaire responses of students about learning using Facebook media. Based on the results of pre test and post test analysis, concluded that the pre test and post test data are normally distributed so that t-test can be performed. Based on the calculation obtained and , because concluded there is influence of the use of Facebook as a medium of learning on student learning outcomes, student responses to learning through the media Facebook can be quite good enough indikasinya is the number of comments from students related to questions posted, as many as 13 students or 76% expressed happy with learning using Facebook, 10 students or 59% who stated more freely in convey opinions, 11 students or 65% who claimed to understand the material using Facebook, 14 students or 82% who expressed interested in solving the problem through Facebook, and 12 students or 71% who said can understand the strategies in solving problems using Facebook. While the obstacles faced by most students are poor networks, limited quota and difficulty in expressing opinions through writing